2013
DOI: 10.1007/s11356-013-1798-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects of nanosilver: impact on castor seed germination, seedling growth, and plant physiology

Abstract: Increasing use of nanoparticles in daily products is of great concern today, especially when their positive and negative impact on environment is not known. Hence, in current research, we have studied the impact of silver nanoparticle (AgNPs) and silver nitrate (AgNO3) application on seed germination, root, and shoot length of castor bean, Ricinus communis L. plant. Silver nanoparticles had no significant effects on seedling growth even at higher concentration of 4,000 mg L(-1), while the silver in bulk form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
85
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(104 citation statements)
references
References 67 publications
17
85
0
2
Order By: Relevance
“…An increase in SOD activity of L. esculentum was reported in AgNPs treated plants (Song et al, 2013). In Ricinus communis, AgNPs treatment enhanced SOD activity up to 1.000 mg/L application; however, it was decreased in 2.000 mg/L AgNPs-treated plants (Yasur and Rani, 2013). Parallel to these studies, high concentration of AgNPs caused a reduction in SOD activity in tomato plants.…”
Section: Discussionmentioning
confidence: 56%
“…An increase in SOD activity of L. esculentum was reported in AgNPs treated plants (Song et al, 2013). In Ricinus communis, AgNPs treatment enhanced SOD activity up to 1.000 mg/L application; however, it was decreased in 2.000 mg/L AgNPs-treated plants (Yasur and Rani, 2013). Parallel to these studies, high concentration of AgNPs caused a reduction in SOD activity in tomato plants.…”
Section: Discussionmentioning
confidence: 56%
“…Activation of the antioxidant system and an increased outflow of electrolytes from tissues was observed by Yasur and Rani (2013) and Hatami and Ghorbanpour (2014). At the same time, other authors have observed an increase in chlorophyll content and increased photosynthetic efficiency caused by nanoparticles (Priyadarshini et al 2012).…”
Section: Discussionmentioning
confidence: 86%
“…However, other studies have shown that phytotoxicity increases with particle size. For example, Yasur and Rani (2013) affirmed that all Ag NP treatment groups had no effect on the growth of castor, but in the treatments where the Ag was used in its bulk form, inhibition was observed. This was confirmed by the work of Lee et al (2010).…”
Section: Factors Affecting Np Phytotoxicitymentioning
confidence: 94%
“…However, another study on castor bean (Ricinus communis) seeds under Ag NPs exposure reported an increased ROS production and associated antioxidant defense mechanisms: promoting peroxidase (POD) and superoxide dismutase enzyme (SOD) activity, and this caused an increase in phenolic acids. Phenols are synthesized in plants for defense against pathogens; therefore, ROS generation in this case may not be viewed as entirely negative as ROS also enhances root elongation up to a certain concentration (Yasur & Rani 2013). …”
Section: Phytotoxicity Mechanism In Plants Induced By Npsmentioning
confidence: 99%